Branched-Chain Amino Acid Oxidation Is Elevated in Adults with Morbid Obesity and Decreases Significantly after Sleeve Gastrectomy. Issue 12 (23rd October 2020) - Tan, Hong Chang; Hsu, Jean W; Kovalik, Jean-Paul; Eng, Alvin; Chan, Weng Hoong; Khoo, Chin Meng; Tai, E Shyong; Chacko, Shaji; Jahoor, Farook
ABSTRACT: Background: Plasma concentrations of branched-chain amino acids (BCAAs) are elevated in obese individuals with insulin resistance (IR) and decrease after bariatric surgery. However, the metabolic mechanisms are unclear. Objectives: Our objectives are to compare leucine kinetics between morbidly obese and healthy-weight individuals cross-sectionally, and to prospectively evaluate changes in the morbidly obese after sleeve gastrectomy. We hypothesized that leucine oxidation is slower in obese individuals and increases after surgery. Methods: Ten morbidly obese [BMI (in kg/m 2 ) ≥32.5, age 21–50 y] and 10 healthy-weight participants (BMI <25), matched for age (median ∼30 y) but not gender, were infused with [U- 13 C6 ] leucine and [ 2 H5 ] glycerol to quantify leucine and glycerol kinetics. Morbidly obese participants were studied again 6 mo postsurgery. Primary outcomes were kinetic parameters related to BCAA metabolism. Data were analyzed by nonparametric methods and presented as median (IQR). Results: Participants with obesity had IR with an HOMA-IR (4.89; 4.36–8.76) greater than that of healthy-weight participants (1.32; 0.99–1.49; P < 0.001) and had significantly faster leucine flux [218; 196–259 compared with 145; 138–149 μmol · kg fat-free mass (FFM) −1 · h −1 ], oxidation (24.0; 17.9–29.8 compared with 16.1; 14.3–18.5 μmol · kg FFM −1 · h −1 ), and nonoxidative disposal (204; 190–247 compared with 138; 129–140 μmol · kg FFM −1 · h −1 ) ( P < 0.017 for all). After surgery, the morbidly obese had a marked improvement in IR (3.54; 3.06–6.08; P  = 0.008) and significant reductions in BCAA concentrations (113; 95–157 μmol/L) and leucine oxidation (9.37; 6.85–15.2 μmol · kg FFM −1 · h −1 ) ( P  = 0.017 for both). Further, leucine flux in this group correlated significantly with IR ( r  = 0.78, P < 0.001). Conclusions: BCAA oxidation is not impaired but elevated in individuals with morbid obesity. Plasma BCAA concentrations are lowered after surgery owing to slower breakdown of body proteins as insulin's ability to suppress proteolysis is restored. These findings suggest that IR is the underlying cause and not the consequence of elevated BCAAs in obesity.